Sexual Dimorphism in Immune Responses and Infection Resistance in Aedes aegypti and Other Hematophagous Insect Vectors - Barletta Ferreira, Ana Beatriz; Bahia, Ana Cristina; Pitaluga, Andre Nobrega; Barros, Erika; Gama dos Santos, Diogo; Bottino-Rojas, Vanessa; Kubota, Marina Sanae; Oliveira, Pedro Lagerblad de; Pimenta, Paulo Filemon Paolucci; Traub-Csekö, Yara Maria; Sorgine, Marcos Henrique Ferreira (Frontiers in Tropical Diseases, 2022)
Sexual dimorphism in immune function is prevalent across different species, where males trade their ability to fight pathogens for a practical reproductive function while females favor an extended lifespan. In insects, these differences in immune function reflect an evolutionary life strategy, where females have a presumably more robust immune system than insect males. Here, we evaluate immune functioning in four male and female insect vectors, Aedes aegypti (Diptera, Culicidae), Anopheles aquasalis (Diptera, Culicidae), Lutzomyia longipalpis (Diptera, Psychodidae) and Rhodnius prolixus (Hemiptera, Reduviidae). We show evidence that challenges the concept of immune sexual dimorphism in three of these insect vectors. In the three Diptera species, A. aegypti, A. aquasalis and L. longipalpis that transmit arboviruses, Plasmodium spp. (Haemospororida, Plasmodiidae) and Leishmania spp. (Trypanosomatida, Trypanosomatidae), respectively, unchallenged adult males express higher levels of immune-related genes than adult females and immature developmental stages. The main components of the Toll, IMD, and Jak/STAT pathways and antimicrobial effectors are highly expressed in whole-body males. Additionally, males present lower midgut basal microbiota levels than females. In A. aegypti mosquitoes, the differences in immune gene expression and microbiota levels are established in adult mosquitoes but are not present at the recently emerged adults and pupal stage. Antibiotic treatment does not affect the consistently higher expression of immune genes in males, except defensin, which is reduced significantly after microbiota depletion and restored after re-introduction. Our data suggest that Diptera males have a basal state of activation of the immune system and that activation of a more robust response through systemic immune challenge acutely compromises their survival. The ones who survive clear the infection entirely. Females follow a different strategy where a moderate immune reaction render higher tolerance to infection and survival. In contrast, hematophagous adult males of the Hemiptera vector R. prolixus, which transmits Trypanosoma cruzi, present no differences in immune activation compared to females, suggesting that diet differences between males and females may influence immune sexual dimorphism. These findings expand our understanding of the biology of insect vectors of human pathogens, which can help to direct the development of new strategies to limit vector populations.